2005
DOI: 10.1016/j.eupc.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

“Cardioneuroablation” – new treatment for neurocardiogenic syncope, functional AV block and sinus dysfunction using catheter RF-ablation

Abstract: Cardiac neuroablation is a new technique for management of patients with dominantly adverse parasympathetic autonomic influence. The technique is based on radiofrequency (RF) ablation of autonomic connections in the three main ganglia around the heart. Their connections are identified by Fast-Fourier Transforms (FFTs) of endocardial signals: sites of autonomic nervous connections show fractionated signals with FFTs shifted to the right. In contrast, normal myocardium without these connections does not show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
277
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(310 citation statements)
references
References 22 publications
4
277
0
11
Order By: Relevance
“…Endocardial GP ablation has been increasingly used to treat severe vagal-related arrhythmias. [8][9][10][11][12][13][14] Although the guidelines 20 indicate pacemaker implantation for cases of symptomatic bradycardia and atrioventricular block, the fact that these patients are mostly young and otherwise healthy individuals encourages a more conservative approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocardial GP ablation has been increasingly used to treat severe vagal-related arrhythmias. [8][9][10][11][12][13][14] Although the guidelines 20 indicate pacemaker implantation for cases of symptomatic bradycardia and atrioventricular block, the fact that these patients are mostly young and otherwise healthy individuals encourages a more conservative approach.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse GP-mapping strategies used by different authors (1, high-frequency endocardial stimulation [2][3][4][5][6][8][9][10][11][12] ; 2, purely anatomic location 7,13 ; and 3, atrial electrogram characteristics 1,10,14,15 ) emerged as potential alternatives, with each one proposing specific end points (1, evoked reflex abolition; 2, ablation of all anatomic GP sites achieved; and 3, elimination of all fragmented potentials, respectively). However, some important questions still remain whichever technique is chosen:…”
Section: See Editorial By Mulpuru and Shenmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the European guidelines on syncope do not recommend the HUTT for patients that have a typical clinical history of VVS, the tilt test is valuable in identifying the type of VVS (cardioinhibitory, vasodepressor or mixed). Some authors recommend different treatment options depending on the type of vasovagal syncope, so in this case, HUTT would serve as therapeutic guidance 5,8 . Pachon et al 8 recently published a new therapeutic alternative for patients with neurocardiogenic syncope, which would be more suitable for patients with cardioinhibitory VVS.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Pachon, et al reported recently that persistent parasympathetic denervation and sympathetic reinnervation after endocardial radiofrequency ablation of autonomic connections in the 3 main ganglia were demonstrated by the permanent modification of the heart rate variability in the chronic phase, leading to amelioration of sinus node function. 14) Recent reports have also shown improved sinus node function after PV isolation. 15,16) Thus, both reverse remodeling of sinus node function and parasympathetic denervation might reduce the recurrence of AF.…”
Section: Vol 48mentioning
confidence: 99%